The Impact of Ability-Enhancing Human Resource Practices on Employees’ Ambidexterity: A Mediation of Cognitive Factors - Gulbahar,; Akhtar, Shazia (International Journal of Psychosocial Rehabilitation, 2020)
The main aim of this study is to empirically validate the impact of ability-enhancing HR practices on employees’ ambidexterity through mediation analysis of their cognitive characteristics. The multi-level data is collected from 400 employees and 80 senior managers of the software companies in Pakistan. The data is analyzed statistically through MPLUS and discloses that the top-down effect of the ability-enhancing HR practices on employees’ ambidexterity is partially mediated by their goal orientation and role breadth self-efficacy. Furthermore, the role of employees’ entrepreneurial orientation is fully mediated in the relationship. This study provides new multi-level insights into the effectiveness of the strategic HR system in supporting employees’ cognitive characteristics and ambidexterity. Moreover, it will be helpful for the management of the software companies in Pakistan to deal with these factors for the enhancement of ambidexterity.